1995
DOI: 10.1180/minmag.1995.059.396.10
|View full text |Cite
|
Sign up to set email alerts
|

Ilvaite from a serpentinized peridotite in the Asama igneous complex, Mikabu greenstone belt, Sambagawa metamorphic terrain, central Japan

Abstract: Ilvaite is sparsely disseminated in a serpentinized plagioclase wehrlite of the Asama igneous complex that underwent the Sambagawa regional metamorphism of pumpellyite-actinolite to greenschist facies. Ilvaite in the Asama complex is monoclinic (a = 13.019(5), b = 8.808(2), c = 5.850(4) A, 13 = 90.19(4)~ and its composition is similar to the ideal end-member composition (CaFe~+Fe3+SizO8OH). Ilvaite occurs in mats of serpentine (chrysotile); it probably formed during serpentinization, which might have accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…On the deepest parts, the mineralogical zonation from barren serpentinite to Fe‐Ca‐silicates to semi‐massive sulphides and then to Cu‐rich MS (Figures e and b) has never been reported before this study. The ilvaite‐andradite‐diopside assemblage has been described in low‐grade metamorphic serpentinites (Agata & Agachi, ) and in oceanic ultramafic settings (Gaggero, Cortesogno, & Gazzoti, ). Gaggero et al () suggested that this assemblage precipitated from early serpentinization‐derived fluids.…”
Section: Discussionmentioning
confidence: 99%
“…On the deepest parts, the mineralogical zonation from barren serpentinite to Fe‐Ca‐silicates to semi‐massive sulphides and then to Cu‐rich MS (Figures e and b) has never been reported before this study. The ilvaite‐andradite‐diopside assemblage has been described in low‐grade metamorphic serpentinites (Agata & Agachi, ) and in oceanic ultramafic settings (Gaggero, Cortesogno, & Gazzoti, ). Gaggero et al () suggested that this assemblage precipitated from early serpentinization‐derived fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Poikilitic ilmenite grain (black) encloses olivine grains that have been entirely altered to serpentine. Serpentine in core of pseudomorph after olivine is associated with fibrous clinopyroxene, chlorite and magnetite that were formed during serpentinization (Agata and Adachi, 1995). Width of field is 1.7 mm.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Mn-rich ilmenite occurs also as veins along cracks in many ilmenite grains, and is apparently not magmatic. Mn-rich ilmenite was found in rims of chromite-ilmenite intergrowth and is associated with "Ferritchromit" (Fe3+-rich Cr spinel formed as the result of alter ation of magmatic chromite; Ramdohr, 1969), which was formed during the Sambagawa meta morphism (Agata and Adachi, 1995). Mn-rich il menite was probably an alteration product during the Sambagawa metamolphism.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations